A glycan-based approach to therapeutic angiogenesis - Chua, Jie Shi (PLoS One, 2017)
Angiogenesis, the sprouting of new blood vessels from existing vasculature, involves multiple complex biological processes, and it is an essential step for hemostasis, tissue healing and regeneration. Angiogenesis stimulants can ameliorate human disease conditions including limb ischemia, chronic wounds, heart disease, and stroke. The current strategies to improve the bioavailability of pro-angiogenic growth factors, including VEGF and FGF2, have remained largely unsuccessful. This study demonstrates that small molecules, termed click-xylosides, can promote angiogenesis in the in vitro matrigel tube formation assay and the ex ovo chick chorioallantoic membrane assay, depending on their aglycone moieties. Xyloside treatment enhances network connectivity and cell survivability, thereby, maintaining the network structures on matrigel culture for an extended period of time. These effects were achieved via the secreted xyloside-primed glycosaminoglycans (GAG) chains that in part, act through an ERK1/2 mediated signaling pathway. Through the remodeling of GAGs in the extracellular matrix of endothelial cells, the glycan approach, involving xylosides, offers great potential to effectively promote therapeutic angiogenesis.